Few-atom cluster model systems for a hydrogen economy. Issue 1 (1st January 2020) - Vanbuel, Jan; Ferrari, Piero; Janssens, Ewald
ABSTRACT: To increase the share of renewable zero-emission energy sources, such as wind and solar power, in our energy supply, the problem of their intermittency needs to be addressed. One way to do so is by buffering excess renewable energy via the production of hydrogen, which can be stored for later use after re-electrification. Such a clean, renewable energy cycle based on hydrogen is commonly referred to as the hydrogen economy . This review deals with cluster model systems of the three main components of the hydrogen economy, i.e. hydrogen generation, hydrogen storage and hydrogen re-electrification, and their basic physical principles. We then present examples of contemporary research on few atom clusters, both in the gas phase and deposited, to show that by studying these clusters as simplified models a mechanistic understanding of the underlying physical and chemical processes can be obtained. Such an understanding will inspire and enable the design of novel materials needed for advancing the hydrogen economy. Abstract :